Economic Impact of Global Water Scarcity: An Overview - Guarino, Arthur S. (Science and Technology: Recent Updates and Future Prospects Vol. 10, 2024)
The aim of this paper is to examine the economic impact of global water scarcity on both developed and developing nations. Water, like any other natural resource, is vital to a nation’s economic growth and existence. Water scarcity is dynamic and complex, emerging from the combined influences of climate change, basin-level water resources, and managed systems’ adaptive capacities. Beyond geophysical stressors and responses, it is critical to also consider how multi-sector, multi-scale economic teleconnections mitigate or exacerbate water shortages. Without adequate water supplies, a nation will face severe economic problems as well as social unrest and political instability. The current problem many nations face is their dwindling water supply. This paper will also examine how a lack of clean water will hurt a nation’s economic growth and its ability to be a viable player in global trade and be able to provide for its people. This study will also look at the causes of water scarcity and how the problem can be rectified. Policymakers and government leaders can act in a clear and decisive manner to improve the infrastructure in their respective cities, towns, states, and countries, global water scarcity will only get worse. Improving infrastructure to provide abundant water is no longer an option, but a vital necessity.